Adaptive interaction torque-based AAN control for lower limb rehabilitation exoskeleton. (September 2022) - Wang, Yu; Wang, Haoping; Tian, Yang
Abstract: In this paper, an adaptive interaction torque-based assist-as-needed (AITAAN) control method for the lower limb rehabilitation exoskeleton is proposed. Firstly, a desired input torque for the wearer's lower limb is designed based on computed torque control (CTC). A nonlinear disturbance observer (NDO) is used to assess the lower limb muscle torque. Subtract the estimated muscle torque from the desired input torque, the exoskeleton only provides the remaining torque through interaction torque. Then, the interaction torque tracking problem can be converted to the exoskeleton trajectory tracking problem by using the spring–damper like dynamics model of the interaction force. A flexible boundary prescribed performance controller (PPC) is designed for the exoskeleton to achieve fast and accurate trajectory tracking. The coupled wearer-exoskeleton system is established in SolidWorks and imported to MATLAB/Simulink with SimMechanics. The AITAAN controller's effectiveness and superiority were then verified through co-simulations. Highlights: This paper develops a novel AITAAN controller for the lower limb rehabilitation exoskeleton. A NDO is utilized to estimate the wearer's muscle torque. A flexible boundary PPC is designed to guarantee fast and accurate tracking performance. The coupled virtual wearer-exoskeleton system is established to show the superiority of the AITAAN.